2013
DOI: 10.1111/are.12356
|View full text |Cite
|
Sign up to set email alerts
|

Growth variations within a farm of mussel (Mytilus galloprovincialis) held near fish cages: importance for the implementation of integrated aquaculture

Abstract: Fish farming releases extensive amounts of particulate organic waste that can be exploited by bivalves in integrated culture. We tested if mussels Mytilus galloprovincialis cultured at two depths (1 and 6 m) in a raft, moored 170 m from a fish farm had greater growth than bivalves held 550 m from the fish cages. Mussel growth was monitored monthly, covering the second phase of the culture, from thinning-out to harvest (March to November 2011). We also studied if fish solid and dissolved nutrients increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
(69 reference statements)
1
9
0
1
Order By: Relevance
“…These results agree with PEHARDA et al (2007), who found the highest growth rates of mussels in period from March to May, which could indicate that the highest growth during the spring period can be the result of increased food aviability. On the other hand, results of this study partly agree with results reported by IRISARRI et al (2014a), who found maximum growth in mussels during both spring and summer period. According to VAN ERKOM SCHURINK & GRIFFITHS (1992) as well as ŽUPAN & ŠARIĆ (2014), highest avaliability of food is at temperatures between 10°C and 20°C, when the recorded mussel growth is most intense, while the growth slows at temperatures above 20°C.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with PEHARDA et al (2007), who found the highest growth rates of mussels in period from March to May, which could indicate that the highest growth during the spring period can be the result of increased food aviability. On the other hand, results of this study partly agree with results reported by IRISARRI et al (2014a), who found maximum growth in mussels during both spring and summer period. According to VAN ERKOM SCHURINK & GRIFFITHS (1992) as well as ŽUPAN & ŠARIĆ (2014), highest avaliability of food is at temperatures between 10°C and 20°C, when the recorded mussel growth is most intense, while the growth slows at temperatures above 20°C.…”
Section: Discussionsupporting
confidence: 93%
“…Integrated multi-trophic farming systems of various marine organisms are known worldwide (FAO, 2009;ABREU et al, 2009;NAVARRETE-MIER et al, 2010;REID et al, 2010;HUGHES & KELLY, 2011;HANDÅ et al, 2012;LANDER et al, 2012;IRISARRI et al, 2014a). The possibility of implementation of the integrated multi-trophic farming in the Mediterranean was well studied in the last ten years (PEHARDA et al, 2007;NAVARRETE-MIER et al, 2010;SARÀ et al, 2011;ŽUPAN, 2012;ŽUPAN et al, 2012;ŽUPAN et al, 2013;ŽUPAN et al, 2014;ISARRI et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…As in shellfish ecology studies, SFG is also common in shellfish aquaculture studies (Navarro et al 1991;Okumus ß & Stirling 1994;Newell et al 1998;Gibbs 2007;Sar a & Pusceddu 2008). Likewise, in IMTA systems SFG has been primarily used to assess the shellfish component (Gao et al 2008;Irisarri et al 2013aIrisarri et al ,b, 2014.…”
Section: Scope For Growth (Sfg)mentioning
confidence: 99%
“…M. galloprovincialis was considered as a suitable prey species for this kind of study with H. trunculus. Using this species as prey provides ease of comparison with the previous studies and more importantly, beside its key role in benthic communities, M. galloprovincialis is a valuable bivalve species and widely cultivated in Mediterranean area (Neofitou et al, 2014;Irisarri, Cubillo, Fernández-Reiriz, & Labarta, 2015) and H. trunculus is considered its pest in some culture areas (Peharda & Morton, 2006). …”
Section: Introductionmentioning
confidence: 99%